Genomic, metabolic and phenotypic variability shapes ecological differentiation and intraspecies interactions of Alteromonas macleodii - Koch, Hanna (2021)
Ecological differentiation between strains of bacterial species is shaped by genomic and metabolic variability. However, connecting genotypes to ecological niches remains a major challenge. Here, we linked bacterial geno- and phenotypes by contextualizing pangenomic, exometabolomic and physiological evidence in twelve strains of the marine bacterium Alteromonas macleodii, illuminating adaptive strategies of carbon metabolism, microbial interactions, cellular communication and iron acquisition. In A. macleodii strain MIT1002, secretion of amino acids and the unique capacity for phenol degradation may promote associations with Prochlorococcus cyanobacteria. Strain 83-1 and three novel Pacific isolates, featuring clonal genomes despite originating from distant locations, have profound abilities for algal polysaccharide utilization but without detrimental implications for Ecklonia macroalgae. Degradation of toluene and xylene, mediated via a plasmid syntenic to terrestrial Pseudomonas, was unique to strain EZ55. Benzoate degradation by strain EC673 related to a chromosomal gene cluster shared with the plasmid of A. mediterranea EC615, underlining that mobile genetic elements drive adaptations. Furthermore, we revealed strain-specific production of siderophores and homoserine lactones, with implications for nutrient acquisition and cellular communication. Phenotypic variability corresponded to different competitiveness in co-culture and geographic distribution, indicating linkages between intraspecific diversity, microbial interactions and biogeography. The finding of “ecological microdiversity” helps understanding the widespread occurrence of A. macleodii and contributes to the interpretation of bacterial niche specialization, population ecology and biogeochemical roles.